1983
DOI: 10.1172/jci110829
|View full text |Cite
|
Sign up to set email alerts
|

Identical Structural and Receptor Binding Defects in Apolipoprotein E2 in Hypo-, Normo-, and Hypercholesterolemic Dysbetalipoproteinemia

Abstract: A B S T R A c T Apolipoprotein E (apoprotein E or apo-E) from type III hyperlipoproteinemic subjects with the E2/2 homnozygous phenotype displays both structural and receptor binding heterogeneity. The apo-E from all subjects thus far studied, however, has been functionally defective, though to different degrees. Although nearly every type 111 hyperlipoproteinemic subject has the E2/2 phenotype, 95-99% of the people with this same phenotype do not display type 111 hyperlipoproteinemia, nor do they have elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
1
2

Year Published

1985
1985
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 36 publications
5
36
1
2
Order By: Relevance
“…78 ' ™ In addition it has been shown that apo E from hyper-, normoor hypocholesterolemic subjects with an E2/2 phenotype has equally defective binding to the LDL receptor in vitro. 80 The data are most consistent with the notion that the E2/2 phenotype is a necessary, but not sufficient, requirement for the expression of type III hyperiipoproteinemia in humans.…”
Section: Dysbetallpoprotelnemla and Type III Hyperiipoproteinemiasupporting
confidence: 77%
See 1 more Smart Citation
“…78 ' ™ In addition it has been shown that apo E from hyper-, normoor hypocholesterolemic subjects with an E2/2 phenotype has equally defective binding to the LDL receptor in vitro. 80 The data are most consistent with the notion that the E2/2 phenotype is a necessary, but not sufficient, requirement for the expression of type III hyperiipoproteinemia in humans.…”
Section: Dysbetallpoprotelnemla and Type III Hyperiipoproteinemiasupporting
confidence: 77%
“…On the other hand, the estimate of the relative frequency of e4 for the Finnish population is 50% higher than the estimates for the other Caucasian populations and significantly different (p < 0.01) from all other samples in the group. There is no statistically significant evidence for heterogeneity of the relative allele frequencies among the Framingham, 80 Munster, 6162 Marburg, 3 Grampian, 57 Ottawa, 54 and Nijmegen 56 populations. The Nancy and Christchurch estimates are not significantly different from each other at the 0.10 level of probability.…”
Section: Relative Allele Frequenciesmentioning
confidence: 91%
“…Collectively, these kinetic defects may account for the dyslipoproteinemia seen in our apoE2/E2 type III hyperlipidemic subjects. Whether downregulation of VLDL receptors or other extrahepatic receptors ( 31,32 ), or the inhibition of lipolytic enzymes by other apoproteins, such as apoC-III ( 33,34 ), contributes further to the impaired catabolism and accumulation of ␤ -VLDL particles in circulation requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…gous for cysteine at position 1S8, 23 and in the second, six of seven apo E2/2 type III patients from a New Zealand population were also found to be homozygous for this substitution. 20 The results are also consistent with the Funke et al study 29 in which DNAs from six apo E2/2 subjects and seven subjects heterozygous for apo E2 were examined with oligonucleotide probes.…”
mentioning
confidence: 90%
“…A limited screening of six German apo E2/2 subjects, who ranged from hypolipidemic to hyperlipidemic, showed that all were homozygous for apo E2(Arg 158 ->-Cys). 23 That study involved protein sequencing, which is not an effective method for screening large populations. One possible alternative method is sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) of VLDL.…”
mentioning
confidence: 99%